Quantifying salinity-induced changes on estuarine benthic fauna: The potential implications of climate change - Little, S.; Wood, P.J.; Elliott, M. (Estuarine, coastal and shelf science, 2017)
Coastal and estuarine systems worldwide are under threat from global climate change, with potential consequences including an increase in salinities and incursion of saltwater into areas currently subject to tidal and non-tidal freshwater regimes. It is commonly assumed that climate-driven increases in estuarine salinities and saline incursion will be directly reflected in an upstream shift in species distributions and patterns of community composition based on salinity tolerance. This study examined the responses of benthos to medium-term salinity changes in two macrotidal river-estuary systems in SE England to test whether these responses may be representative of climate-induced salinity changes over the long-term. The study reinforced the effect of salinity, related to tidal incursion, as the primary environmental driver of benthic species distribution and community composition. Salinity, however, acted within a hierarchy of factors followed by substratum type, with biotic competition and predator-prey relationships superimposed on these. The assumption that increasing salinities will be directly reflected in a shift in species distributions and patterns of community composition upstream over the long-term was shown to be over simplistic and not representative of a complex and highly variable system. Relative Sea Level Rise (RSLR) projections were predicted to increase estuarine salinities and saline incursion in the study estuaries, which together with projected reductions in river flow will have important consequences for estuarine structure and function, particularly in tidal limnetic zones, despite estuarine communities being pre-adapted to cope with fluctuating salinities. The study identified, however, that limnic-derived fauna inhabiting these zones may demonstrate greater tolerance to salinity change than is currently recognised, and may persist where salinity increases are gradual and zones unbounded.